EFFECT OF PROFENOFOS ON THIOBARBITURIC ACID REACTIVE SUBSTANCES, SCAVENGING ENZYMES AND GLUTATHIONE IN THE BRAIN OF ALBINO RAT - V.UMAKANTHI; M. SREEKANTH; M. JAYASUDHA; S.V. RAVIKANTH; P. JACOB DOSS (International Journal of Pharma and Bio Sciences, 2014)
By late the development and use of organophosphate (OP) compounds has gained huge mileage than before and this trend is like to continue in the years ahead. This is because new applications for many OPs have been discovered. Nevertheless, indiscriminate and excessive use of these pesticides is causing havoc to non-target organisms. Oxidative stress has recently been implicated as a factor in the mortality and morbidity induced by OP compound poisoning. Hence oxidative stress was studied in the Albino rats exposed to Profenofos. They were evaluated for oxidative stress markers MDA (end product of lipid peroxidation) and reduced glutathione (GSH). The effect of 1/10th of LD50 of Profenofos (i.e. 39.5mg/kg body weight) was studied in different regions of the brain of Albino rat after exposure to 10, 20 and 30 days respectively. All the animals were administered with Profenofos on alternate days. From the results it is clear that xanthine oxidase, superoxide dismutase, catalase and lipid peroxidation activities showed a steady increase in all the regions of the brain with maximum increase in 30 days exposed animals clearly indicating that the effect of Profenofos is more when the animals are repeatedly exposed to this chemical. Glutathione peroxidase and glutathione reductase activities showed a sharp decline in all the regions of the brain in a time dependent manner. It was concluded on the basis of biochemical analysis that profenofos exposed rats are prone to more oxidative stress as evidenced by the changes in antioxidant status. The measurement of these substances in non-target organisms and agricultural workers who spray OPs could be a good biomonitoring factor and is recommended to be performed on a regular basis. The present study clearly indicates that Profenofos has serious impact on the non-target organisms and should be used with great caution.